Urinalysis in primary care doctor practice - Bartlomiej Szewczyk; Kamila Szewczyk; Paulina Pytel; Wiktoria Julia Krzesłowska; Weronika Hołownia; Szymon Wiśniewski (Kazimierz Wielki University, 2024)
Introduction: A urinalysis is a simple diagnostic test which is used to detect wide range of disorders including urinary tract infections, kidney disease and diabetes. Moreover, it can be an useful tool to monitor a medical condition. A urine analysis might be a part of routine medical exam in order to check patient's health condition but it is not recommended as a preventive screening test in the population. We believe that this article will contribute to spreading important knowledge especially in primary care. Aim of the study: The aim of the article is to collect and summarize basic information on urinalysis. We collected elemental information about routine urine examination, which includes assessment of physical properties, chemical properties and sediment composition. This knowledge is useful in the daily practice of a primary care doctor. Material and methods: Literature available in the PubMed database, ScienceDirect and ClinicalKey was reviewed using the following keywords: "Urinalysis";  "Urine sediment", "Urinary tract infection" Conclusions: The ability of proper urine analysis is crucial in clinical practice. Performing the test is technically simple and widely available. It is important to be aware of the limitations of urine analysis. Therefore if results of urinalysis is unusual, it is necessary to require more testing to find the source of the medical issue.